Abrasiveness of denture cleaners - Lampa, Kathrene Faye O.; Punzalan, Aaron M.; Magtanong, Danilo (Adviser).
It is the dentist's job to provide for the denture, but the cooperation of the patient is needed for the proper maintenance of the prosthesis. Though denture wearers possess the knowledge on how to clean their prosthesis, the various agents used to clean their dentures may have certain consequences that affect the denture. One of these is abrasion that may cause distortion and ill fit of the denture. The aim of the study was to determine if there was a difference in weight of the denture base and this difference would mean abrasion done on the denture by the different denture cleaners. Seventy-two 75 cm3 heat cured acrylic resin plates were divided into 4 groups, one group for each type of denture cleaner (denture dentifrice, regular toothpaste, bath soap and detergent). They were further divided into 3 groups, one for each stroke (5,000, 10,000 and 20,000). Each plate was weighed before and after it was subjected to brushing. The weight difference of the individual plates for each stroke far each denture cleaner was recorded, added, and then the mean was taken. Based on the analyzed data, detergent had the greatest mean amount of weight reduced while bath soap had the least mean amount, though the effect of the type of denture cleaner on the amount of weight reduced cannot be established statistically. It is also revealed in the results that as there is an increase in the number of strokes, there is a reduction in weight.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Denture cleansers; Teeth -- Abrasion; Tooth abrasion